Development of Bacillus strain B12 and B45 as putative probiotics to improve growth and survival of Epinephelus fuscoguttatus (Forsskal, 1775) juvenile challenged with vibrio alginolyticus - Abd Razak, Nabilah Fatin (2015)
Occurrences of bacterial diseases and the overexploitation to overcome it have resulted to the emergence of antibiotic resistant microorganisms. In relation to this matter,experiments were performed in this study by identifying putative probionts, screening of putative probionts against selected pathogenic strains based on their in vitro antagonism activities, in vivo safety test, feeding trial of E. fuscoguttatus juveniles and challenge with V. alginolyticus. Gram’s method had classified 44 bacterial strains as rod, gram positive cells while biochemical test (BBL CrystalTM identification system) had identified 44 bacterial strains to species level. From 44 bacterial strains, 22 were non-haemolytic isolates. Agar well diffusion assay have demonstrated two bacilli strains; B12 and B45 elucidating intermediate (++; 11 mm – 15 mm) to highest level (+++; >16 mm) of inhibition zones against Vibrio alginolyticus, V. parahaemolyticus,V. harveyi and Aeromonas hydrophila. The broth culture assay in this study observed a complete inhibitory activity of Bacillusstrain B12 towards V. alginolyticus at preincubation cell density of 105 and 107 cfu/mL while Bacillus strain B45 have displayed no inhibitory activity. 16S rRNA gene sequencing have identified Bacillus strain B12 as Bacillus amyloliquafaciens (94% similarity) and Bacillusstrain B45 as Bacillus subtilis (95% similarity). Pathogenicity test of Bacillus strain B12 and B45 by intraperitoneal (IP) injection have revealed no sort of abnormalities or mortalities on E. fuscoguttatus juveniles. Supplementation of Bacillus strain B12 into feed of E.fuscoguttatus juveniles showed an efficient feed conversion ratio (FCR) of 1.17 + 0.07, increased specific growth rate (2.66 + 0.23) and survival (98 + 1.73%). Application of Bacillus strain B12 into daily feed had significantly increased survival (P<0.05) to 71.65% when E. fuscoguttatus juveniles were challenged with V. alginolyticus. To summarize, experimental findings in this study showed that Bacillus strain B12 at cell density of 107 cfu/mL have the potential to be used as feed additive to improve growth and survival of E. fuscoguttatus juveniles.